2017
DOI: 10.1038/nchembio.2493
|View full text |Cite
|
Sign up to set email alerts
|

Stendomycin selectively inhibits TIM23-dependent mitochondrial protein import

Abstract: Tim17 and Tim23 are the main subunits of the TIM23 complex, one of the two major essential mitochondrial inner-membrane protein translocon machineries (TIMs). No chemical probes that specifically inhibit TIM23-dependent protein import were known to exist. Here we show that the natural product stendomycin, produced by Streptomyces hygroscopicus, is a potent and specific inhibitor of the TIM23 complex in yeast and mammalian cells. Furthermore, stendomycin-mediated blockage of the TIM23 complex does not alter nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Stendomycin reduced the import of proteins into the IMM, IMS, and matrix by Tim23 both in vitro and in vivo. However, interestingly, it had no effect on steady-state PINK1 import (Filipuzzi et al, 2017), which is consistent with our Tim23 knockdown experiments. Recent analysis of another PARL substrate, STARD7, also revealed that PARL-mediated STARD7 cleavage was observed after Tim23 knockdown (Saita et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Stendomycin reduced the import of proteins into the IMM, IMS, and matrix by Tim23 both in vitro and in vivo. However, interestingly, it had no effect on steady-state PINK1 import (Filipuzzi et al, 2017), which is consistent with our Tim23 knockdown experiments. Recent analysis of another PARL substrate, STARD7, also revealed that PARL-mediated STARD7 cleavage was observed after Tim23 knockdown (Saita et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Analogous to the development of small compounds to enhance PINK1 kinase activity as a potential treatment for PD (Hertz et al, 2013), manipulation of PINK1 import may be another druggable target to augment PINK1 activity. Among such drug screens, stendomycin, a natural lipopeptide produced by Streptomyces hygroscopicus, has been recently identified as an inhibitor of Tim23-dependent mitochondrial protein import (Filipuzzi et al, 2017). Stendomycin reduced the import of proteins into the IMM, IMS, and matrix by Tim23 both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our data emphasize that this technique is useful to study the involvement of other proteins, such as Sirt3 and Sirt5, in the retrograde signaling pathway with high resolution. We also highlight that this approach is applicable to screen compounds that target mitochondrial protein import, such as stendomycin [31].…”
Section: Discussionmentioning
confidence: 99%
“…Further validation of kinetin activity, especially in vivo, is expected. Although the activation of PINK1 kinase activity is closely related to its import regulation, as discussed above, there are no reports of small molecules targeting PINK1 import so far, although attempts are being made in this promising new direction [ 82 ].…”
Section: In Vivo Relevance and Potential For Drug Discoverymentioning
confidence: 99%